BSS552: Construction Technology II/ College of Built Environment - UiTM, / College of Built Environment (2017)
This course is aimed to cover in detail the various elements and method of construction of industrial and commercial buildings. The topic ranges from concrete production to foundation, walls and roofs, taking into account the construction method, assembly technique of different materials, components and choice of materials.